The Influence of Shared Intentions With Others in Physical and Cognitive Tasks That Require Collaborative Solving in Elementary School - Kano, Takahiro; Yokoyama, Keiko; Yamamoto, Yuji (Frontiers in Education, 2022)
Developing the competence to share intentions with others is an important role of elementary schools for the children’s future well-being. This study aims to analyze and clarify the relationship between physical and cognitive tasks that require collaborative solving to cultivate skills to share intentions with others through human movement. As a physical task, we designed a tag game in which two defenders prevented the penetration of the three attackers to reach the goal line. We focused on the movement of the defenders in the game and analyzed the efficiency of their individual movement as an individual behavior and the interpersonal distance between two defenders as a pair behavior. As a cognitive task, we examined paired activities when understanding concepts in math classes. We observed talking and listening behaviors during the pair activities and analyzed the responsive behavior as an individual behavior, which consisted of the responsive utterance in the content of utterances and active listening from the gaze direction of the listener. In addition, role change during pair activities in math lessons was analyzed as pair behavior. We then analyzed the relationship between behaviors in both tasks. The hypotheses were as follows: (1) task constraints lead to interaction between individual and pair behavior in both tasks; and (2) individual and paired behaviors between the two tasks show similar characteristics. As a result, the first hypothesis was supported in both tasks: the efficiencies of individual movement, interpersonal distances in the game and the frequencies of responsive behavior and role changes in pair activities in math were positively correlated. The second hypothesis was also supported: the individual and pair behaviors between the two tasks showed significant correlations. This suggests that the competence to share intention with others would be fundamental regardless of the physical and cognitive tasks. The study posits that task constraints of joint action in physical education lead to an understanding of the task goals and exploring the solution by win and loss. These experiences might be generalized to all cognitive tasks to cultivate the competence to share intentions with others.